Plant Community Composition and Species Diversity in the Alpine Meadows of Uttaranchal Himalayas - Kala, Chandra Prakash (Indian Forester, 2006)
The alpine meadows of the Uttaranchal Himalayas are well known for rich floral and faunal diversity. In order to study the alpine meadows of Uttaranchal Himalayas, the Valley of Flowers National Park (VOF; protected from livestock grazing) and the Khiron Valley (seasonally grazed by livestock) were selected. This paper reports plant community composition and species diversity in the VOF and Khiron Valley using stratified random quadrats of 0.25 m2. TWINSPAN was used for identifying the plant communities and Shannon Wiener Index (H’) was used for species diversity. The central valley portion in the VOF that falls between 3,300-3,700m elevations obtained 9 plant communities whereas the Khiron Valley, located at similar elevation, obtained only 7 plant communities. In VOF, species diversity was higher (H’=2.93) than the Khiron Valley (H’=2.77). Plant species diversity decreased with elevation in both protected and unprotected alpine meadows. The results are discussed along with the management implications.